The Effects of Virtual Reality Application on Pain Intensity, Anxiety Level and Patient Satisfaction in Patients Who Undergo Bronchoscopy: A Randomized Controlled Trial - Sarikose, Aysegul; Turan, Gulcan Bahcecioglu (Elsevier Science Inc, 2025)
Background: Bronchoscopy is a medical procedure that allows imaging of the airways and lungs. With the help of a light and camera at its tip, the bronchoscope device can enter the airway and provide real-time visualization. Since most patients are conscious during the bronchoscopy procedure, they may experience pain and anxiety regarding possible complications and an uncertain outcome. Aim: This study was conducted to determine the effects of virtual reality (VR) application on pain intensity, anxiety level, physiological symptoms of anxiety (vital signs) and patients' satisfaction level with the use of virtual reality while undergoing a bronchoscopy. Design: A parallel randomized controlled trial. Setting: Bronchoscopy unit of the chest diseases service of a 1053 bed university hospital in eastern Turkey. Sample and Methods: The study was conducted with a total of 70 patients, 35 in the intervention group and 35 in the control group. The researcher interviewed patients and approved those who met the research criteria and agreed to participate in the study. The researcher applied relaxation exercises to the patients in the intervention group using virtual reality glasses for 5 minutes before the procedure and 4-5 minutes during the procedure. No interventions were made for the patients in the control group. Data were collected using the Descriptive Information Form, Visual Analog Scale (VAS), Anxiety Assessment Scale (AAS), Physiological Symptoms of Anxiety Follow-up Form, and Virtual Reality Glasses Application Satisfaction Form. Results: When compared with the control group, the mean scores of VAS, AAS, heart rate, diastolic and systolic blood pressure, and respiratory rate of the intervention group were found to decrease significantly, while the O-2 saturation value increased significantly (p < .05). It was found that 82.5% of the patients in the intervention group want to use virtual reality glasses if they have another intervention, and 70% recommend relaxation exercises with virtual reality glasses to patients who will undergo bronchoscopy. Conclusion: Study results for this sample revealed that the use of VR decreased pain intensity scores, state anxiety levels, anxiety severity, diastolic blood pressure, systolic blood pressure, heart rate and respiratory rate, and increased O-2 saturation in patients who underwent bronchoscopy. In line with these results, VR should be considered during bronchoscopy procedures. (c) 2024 American Society for Pain Management Nursing. Published by Elsevier Inc. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Anxiety; Bronchoscopy; Patient; Pain intensity; Virtual reality